Perceived Opportunity and Risk Control Role on Willingness to Recommend Sharia Fintech - Riofita, Hendra (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2024)
This study aims to improve Muslim MSME customers’ willingness to recommend other Muslims to use Sharia Fintech to purchase MSME products at Sharia marketplaces through perceived opportunity and perceived risk control. The data processed with SPSS and Amos program were collected through a questionnaire in the form of Google link sent to the respondents with experience using Sharia Fintech to purchase MSMEs products at Sharia marketplaces. Findings demonstrate that all hypotheses are supported and that the relationship among constructs within the framework of TAM and the Theory of Reasoned Action can be elaborated in the context of the use of Sharia Fintech at Sharia marketplaces.